Whole genome sequencing and functional annotation of Fusarium oxysporum f. sp. lentis to unravel virulence and secondary metabolite biosynthesis gene clusters - Kharte, Sanjay; Kumar, Ashish; Mishra, Priyamvada; Ramakrishnan, R. S.; Sharma, Stuti; Mishra, Nishi; Chauhan, Puneet Singh; Sharma, Radheshyam; Gautam, Vedant; Tiwari, Shweta; Goyal, Vinod; Sharma, Sonu; et al. (Frontiers in Genetics, 2025)
BackgroundFusarium oxysporum f. sp. lentis is a major fungal pathogen that causes vascular wilt in lentil crops, leading to significant reductions in yield. Despite its importance, the genetic underpinnings of this pathogen remain poorly understood.MethodsWe performed whole-genome sequencing of F. oxysporum f. sp. lentis using the Illumina Shotgun Sequencing platform. The resulting high-quality genome assembly consisted of 12,366 contigs with a total length of 124.48 Mb. Genome completeness was evaluated using Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis, and functional annotation was performed through comparisons with several public databases, including Uniprot, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), Pfam, and Clusters of Orthologous Groups (COG). Pathogenicity-related genes were identified using the PHI-base database, and secondary metabolite biosynthesis was analyzed with AntiSMASH.ResultsThe genome assembly achieved 99% completeness, identifying 116,998 protein-coding genes. A total of 16,779 carbohydrate-active enzymes (CAZymes) could be detected, highlighting the pathogen’s potential for plant cell wall degradation. Pathogenicity analysis revealed genes linked with moderate virulence. AntiSMASH detected 77 biosynthetic gene clusters (BGCs), including those encoding Type I polyketide synthases (T1PKS) and non-ribosomal peptide synthetases (NRPS), which may contribute to pathogenicity.Discussion:The comprehensive genomic analysis of F. oxysporum f. sp. lentis offers valuable insights into its pathogenic mechanisms, including plant cell wall degradation and secondary metabolite production. These findings pave the way for future research on host-pathogen interactions and the development of targeted disease management strategies.